Quantificação de bactérias totais e esporuladas no solo - Vieira, Francisco Cleber Sousa [UNESP]; Nahas, Ely [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2000)
Este trabalho analisou o efeito da temperatura e período de incubação e da diluição do inóculo, em dois meios de cultura, sobre a quantificação de bactérias totais e esporuladas. O crescimento quantitativo e qualitativo de bactérias totais e esporuladas depende tanto do meio de cultura, temperatura, diluição e tempo utilizados como da interação desses fatores. O meio de TSA apresentou maior contagem que o meio de Thorton de unidades formadoras de colônias (UFC) de bactérias totais mas não de Bacillus spp. As colônias crescidas no meio de TSA apresentaram maior tamanho e forma mais nítida. O cultivo à temperatura de 30°C propiciou maior número de UFC que a 25°C, sobretudo nos primeiros dias de incubação. O crescimento bacteriano correspondeu a uma equação de 3° grau. Dependendo do meio de cultura, da temperatura de incubação e da diluição, os períodos de máximo crescimento foram de 4,9 a 6,9 dias para as bactérias totais e de 4,4 a 7,2 dias para Bacillus spp. Embora tenham sido utilizadas diluições decimais dos inóculos, as proporções entre as contagens variaram de 6,3 a 10,0 vezes para as bactérias totais e de 2,0 a 7,0 para as esporuladas.

This work studied the effect of the temperature and incubation time and of the inoculum dilution, in two culture media, on the quantification of total and sporulating bacteria. The quantitative and qualitative growth of total and sporulating bacteria depended on the growth medium, temperature, dilution and incubation time, as well as on the interaction of these factors. Tryptic Soil Agar medium presented a greater number of colony forming units (CFU) for total bacteria. However, for Bacillus spp. there were higher counts on Thorton medium. Colonies grown on Tryptic Soy Agar medium were of larger size and had a more clearly defined shape. An incubation temperature of 30°C yielded more CFU than incubation at 25°C, especially during the first days of incubation. Bacterial growth was fit to a mathematical model and corresponded to a third degree equation. Depending on the growth culture medium, incubation temperature and dilution, periods of maximum growth were between 4.9 and 6.9 days for total bacteria and between 4.4 and 7.2 days for Bacillus spp. Although decimal inoculum dilutions were used, proportions between counts based on different conditions ranged from 6.3 to 10.0 times for total bacteria and from 2.0 to 7.0 times for sporulating bacteria.
Quantification of total and sporulating bacteria in soils
Keywords: Bacillus spp.; total bacteria; soil; Bacillus spp.; bactérias totais; Solo